DETERMINASI TINGKAT SUKU BUNGA DASAR KREDIT MIKRO (STUDI KASUS PADA BANK BUMN DAN BANK UMUM SWASTA NASIONAL DI INDONESIA PERIODE MARET 2013 – OKTOBER 2014) - Sulistyawati, Indah; Galuh, Ajeng Kartika (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to find out the effect of cost of loanable fund, overhead cost, MSME’s risk  and  loan  to  deposite  ratio  on  micro  base  lending  rate  in  state  owned  bank  and  foreign exchange commercial bank.   Panel data  regression  is used  to analyze  this data  research. Using this method,  it can be analyzed  the  impact of    factors which are determines micro base  lending rate in fixed effect model. The results of this research are only MSME’s risk is determining micro base  lending  rate  in  state  owned  bank  and    foreign  exchange  commercial  bank’s  micro  base lending rate is determined by overhead cost, MSME’s risk and loan to deposite ratio. Keyword: Micro Base Lending Rate, Cost of Loanable Fund, Overhead Cost, MSME’s risk, Loan to Deposite Ratiio, Panel Data Regression.